HPLC Method for the Simultaneous Determination of Paracetamol, Aceclofenac and Tizanidine Hydrochloride - Somasekhar, Vanita; Gowrisankar, Dannana (Asian Journal of Chemistry, 2010)
A novel and simple HPLC method was developed and validated for the simultaneous determination of paracetamol, aceclofenac and tizanidine hydrochloride in pharmaceutical preparations. The optimum separation for these analytes was achieved in less than 11 min with a Phenomenex Microsorb-MV 100 C18 column and a mobile phase containing methanol, water, terahydrofuran and orthophosphoric acid in the ratio 560:400:40:1. Detection wavelength was set at 290 nm. The method was suitably validated with respect to specificity, linearity, limit of detection and quantification, accuracy, precision and robustness and was successfully applied to the simultaneous determination of paracetamol, aceclofenac and tizanidine hydrochloride in pharmaceutical preparations.